Examining the Effects of Caffeine Supplementation on the Arousal of University Football Players - Mohy ud Din, Badar; Butt, Muhammad Zafar Iqbal; Tabassum, Yasmeen (Pakistan Journal of Humanities and Social Sciences, 2023)
It is generally known that caffeine has ergogenic characteristics and research has shown that it can improve both the physical and technical aspects of a player's performance. The objective of this study was to discover the impact of caffeine on arousal of male university football players in the South Punjab zone of Pakistan. A randomized placebo controlled, single blind parallel group design was used to perform the study. A total of (n=120) players were selected for the study (age: 22.39 ± 1.69 Years; Height: 172.9 ± 5.85 cm; Body mass 70.12 ± 5.03 kg; Body mass index: 23.45 ± 1.43 kg/m2 Mean ± SD) were distributed into n=4 groups (n=30 in each group) to identify the effect of caffeine on the arousal of the players. In this study (n=3) various doses of caffeine in capsule form were given to three experimental groups. Group A was administered caffeine at 3 mg/kg-1 (LD-CAF: 3 mg/kg-1). Group B was administered caffeine at 6mg/kg-1 (MD-CAF: 6mg/kg-1). Group C was administered caffeine at 9 mg/kg-1 (HD-CAF: 9 mg/kg-1). Whereas, group D was considered a placebo control (PC) group, administered zero mg of caffeine (CAF: 0 mg/kg-1). Felt Arousal Scale (FAS) survey was completed in pre and post-test. Overall, all experimental groups had prominent effects (P < 0.001) on the arousal of male university football players. Results also indicated that a high dose (HD) of caffeine 9mg/kg-1 was more effective (131%) than others.